Spectrum of Human Growth Hormone Receptor Gene Polymorphisms in Physiological Obese Subjects in Babylon Province, Iraq - Hamzah H. Kzar (Journal of Global Pharma Technology, 2016)
Background: A peptide hormone that stimulates growth, cell reproduction, and cell regeneration in humans and other animals is called growth hormone. In human, growth hormone gene is encoded the protein growth hormone receptor that located on chromosome number 5. Obesity is a condition in which excess fat has accumulated in the body, such that it can have an adverse effect on health. Obesity is defined as a body mass index (BMI) of greater than 30 kg/m2. Aim: assessment of spectrum of human growth hormone receptor (HGHR) gene polymorphisms in obese subjects in Babylon province, Iraq. Subjects and Methods: this case-control study included two groups, the first 30 obese subjects (OS) and 30 non-obese subjects (NOS). We investigated GHR genetic polymorphism in both study groups by assessment of the genotyping, Fl/Fl, F1/D3, and D3/D3 of two alleles of GHR. We used allele specific PCR method to investigate the all genotypes and comparing the results with the levels of GH and leptin in serum of study groups. Results: the results of present study showed significant differences (p-value< 0.05) in levels of leptin (LEP) and human growth hormone (HGH) between OS and NOS groups. The genetic results suggested that F1/F1 genotypes have high prevalence in OS compare to NOS (odd ratio was 3.54, CI 95% 1.77-7.94). Conclusion: F1/F1 genotypes have higher levels of leptin and HGH and so it having more risk factor to induce obesity in Babylon population. Keywords: Human growth hormone, growth hormone receptor, obesity, leptin.